Pengaruh Kosentrasi Mutagen Sodium Azida (NaN3) terhadap Daya Kecambah dan Keragaan Bibit Padi Gogo Varietas Jambek Rotan Generasi M-1 - Nurhidayah, Tengku; Ali, Muhammad; Dhamila, Asha (Jurnal Agro Teknologi Tropika, 2017)
The experiment aims to observe the effect of mutagen concentration of sodium azide to the germination and seedling growth performance of upland rice varieties Jambek Rotan generation M-1 and the difference seedling growth of upland rice varieties Jambek Rotan on the generation of M-1 by application Sodium azide some mutagen concentration. The experiment was conducted in an area behind the Soil Laboratory , Faculty of Agriculture , University of Riau , from May to July 2015. Research arranged experimentally using a Completely Randomized Design (CRD), which consists of 5 treatments concentration of sodium azide (SA) , ie 0.0 mM SA , 0.5 mM SA, 1.0 mM SA, 1.5 mM SA and 2.0 mM SA and each treatment was replicated four times. Parameters observed were the percentage of live seedling , seedling height, number of leaves and the number of tillers. The results showed that the of sodium azide at a concentration of 2.0 mM produce the lowest percentage life seedling, but tended to produce the lower seedling height and the more number of tillers.